Are there sex differences in visceral sensitivity in young healthy men and women?. Issue 9 (13th June 2019) - Icenhour, Adriane; Labrenz, Franziska; Roderigo, Till; Siebert, Carsten; Elsenbruch, Sigrid; Benson, Sven
Abstract: Background: Visceral hypersensitivity plays a key role in the pathophysiology of chronic visceral pain like irritable bowel syndrome (IBS), which is significantly more prevalent in women. Possible sex differences in visceral sensitivity remain poorly studied. We assessed sex differences in visceral sensitivity and their association with subclinical symptoms, trait anxiety, and chronic stress in a large sample of healthy men and women. Methods: In 280 young healthy volunteers (50% female), visceral sensory and pain thresholds were determined using rectal balloon distensions. Gastrointestinal (GI) symptoms, chronic stress, and trait anxiety as IBS‐related risk factors were assessed with questionnaires. Men and women were compared regarding visceral sensitivity and multiple regression analyses were conducted to evaluate the predictive value of sex and risk factors for visceral sensitivity. Subgroups with high, intermediate, and low sensitivity were compared regarding psychological and biological characteristics. Key Results: Men and women did not differ in sensory or pain thresholds or in IBS‐related risk factors. In multiple regression analyses, no predictor of visceral sensitivity could be identified. While sensitivity subgroups differed in sensory and pain thresholds, the proportions of men and women were comparable, and groups did not differ in IBS‐related risk factors. Conclusions and Inferences: Despite the large sample size, we found no evidence supporting sex differences in visceral sensitivity. At least in healthy young volunteers, our findings suggest that sex, GI symptoms, anxiety, or chronic stress do not contribute to altered visceral sensitivity. Abstract : Visceral hypersensitivity plays a key role in the pathophysiology of chronic visceral pain like irritable bowel syndrome (IBS), which is significantly more prevalent in women. However, possible sex differences in visceral sensitivity remain elusive. In a large sample of young healthy men and women, we found no evidence supporting sex differences in visceral sensory or pain thresholds, and gastrointestinal symptoms, anxiety, or stress did not predict variation in visceral sensitivity. At least in young healthy volunteers, female sex does not appear to contribute to lowered visceral sensitivity.